RCS and stealth performance analyses of marine low-altitude helicopter - LIANG Chengliang; FEI Zhongyang; ZHAO Qijun; CHEN Xi (Hangkong gongcheng jinzhan)
The study of radar target characteristics and stealth performance of low altitude helicopters at sea can provide a basis for path planning. a random rough sea surface model is established in this paper. Based on the high frequency approximation method, the radar target characteristics of helicopters flying at low altitude on the sea are analyzed. The radar cross section(RCS) of isolated helicopters, the composite electromagnetic scattering of helicopters in the background of sea surface environment, the radar stealth performance of offshore helicopters at different flight heights are studied, and the influence rules are summarized. The results show that under direct radar wave conditions, a strong scattering source is formed at the large curvature radius of the helicopter surface, exhibiting a high RCS. When helicopter is flying at sea, as the flying altitude increases, the coupling effect between the helicopter and the sea weakens, their composite electromagnetic scattering gradually approaches that an isolated helicopter. When helicopter fly at sea, it can lower their altitude to shorten the exposure distance and to some extent avoid enemy radar tracking, achieving stealth penetration.